PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PT INTERNATIONAL BEARINGS - Selamat,; Suhardi, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
With current business developments, there are many opportunities and challenges in the field of business for a company. A company must be able to compete with other companies so that the company can survive and the company must also know what consumers want. This research was aims to determine the effect of brand image and product quality on purchasing decision in PT International Bearings. The research using quantitative methods with validity and reliability testing, correlation coefficient tests, multiple regression tests, partial correlation coefficient tests, t tests and F tests. Total number of samples in this study were 106 people. The questionnaire was distributed to respondents was 106 respondents. Saturation sampling technique was used to determine the sample, which means all members of the population are used as samples. Data analyzed using multiple linear regression analysis. The result of this research indicate that the brand image variable has no effect on purchasing decision with a t count value -1,445 < t table 1,98260 and a significance of 0,152 > α = 0,05. Product quality variable has a positive effect on purchasing decision with a t count value 17,409 > t table 1,98260 and a significance of 0,000 <  α = 0,05. The brand image and product quality variables together have a positive and significance effect on purchasing decision with a Fcount value 153,568 > F table 3,08 and a significance of 0,000 <  α = 0,05.